THE USE OF EDMODO FOR TEACHING SPEAKING IN MASTERING INTERPERSONAL DIALOGUE IN A BLENDED LEARNING SETTING - Yuana Lestari; Anni Hollila Pulungan; Anggarini Thesisia Saragih (Universitas Negeri Medan, 2020)
This study was aimed to describe the use of Edmodo in teaching speaking in mastering interpersonal dialogue in MAN 3 Langkat. The participant of this reserach was Students of grade eleventh in Science class of MAN 3 Langkat. The technique of collecting data used was observation,interview and test. In blended learning, there were two activities which consist of online learning activities which were done using Edmodo and traditional face to face activities which were done in the class. There were five components of speaking they were Organization, Fluency, Pronunciation, Vocabulary, and Performance. The research finding found that Edmodo could help the students to improve their speaking ability especially asking and giving opinion. And then, the result of students’ speaking belongs to good category. Generally, students give the positive response toward the implementation of Edmodo for teaching speaking in asking and giving opinion. Keywords : Edmodo, Blended Learning, Teaching Speaking